2018
DOI: 10.24893/jkma.v12i2.371
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Flood Disaster With The Incidence Of Diarrhea, Water Quality And Community Resilience in Water Supply: A Case Study in The City of Bukittinggi

Abstract: Bukittinggi is a city in West Sumatra that become potential area for flooding. It is followed by increasing of diarrhea diseases. This also affects water quality. Bukittinggi is having problems with the provision of adequate clean water in accordance with the target of Sustainable Development Goals. This study aims to determine the relationship of floods to the incidence of diarrhea, water quality and community resilience in providing clean water for everyday life. The method used through a quantitative approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…As a result, the contribution of the FO process carried out by the drinking water bag in eliminating the E. coli was insignificant. Nonetheless, the process could be very helpful to sterilize the water from microbial content during an emergency, where the level of contamination was expected to be high [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the contribution of the FO process carried out by the drinking water bag in eliminating the E. coli was insignificant. Nonetheless, the process could be very helpful to sterilize the water from microbial content during an emergency, where the level of contamination was expected to be high [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seperti yang disampaikan oleh Paterson, Wright, dan Harris (2018), bahwa masalah kesehatan yang sering terjadi pada bencana banjir adalah gastroenteritis salah satunya. Kejadian diare, kesulitan air, kualitas air (air yang berbau, kotor dan adanya serangga dan cacing) (Sari dan Nofriya, 2018), akan menimbulkan banyak masalah kesehatan sehingga perlu meningkatkan ketahanan masyarakat untuk saling membantu dalam penyediaan air dan penyimpanan sumber air untuk menghindari kontaminasi. Perlunya pendidikan kesehatan khususnya tentang penyediaan air bersih untuk mencegah diare dengan persiapan masyarakat siap dalam menghadapi bencana.…”
Section: Pembahasanunclassified
“…Furthermore, research conducted in Western Uganda bordering a flooded river showed that extreme flooding increased malaria incidence by approximately 30% compared to villages far from the river [11]. Additionally, other researchers also proved that flooding could also endanger human health through infection in wounds [12], diarrhea [13]- [15], and post-traumatic stress disorder among refugees [16].…”
Section: Introductionmentioning
confidence: 99%